A web-based software tool for participatory optimization of conservation practices in watersheds. (July 2015) - Babbar-Sebens, Meghna; Mukhopadhyay, Snehasis; Singh, Vidya Bhushan; Piemonti, Adriana Debora
Abstract: WRESTORE (Watershed Restoration Using Spatio-Temporal Optimization of Resources) is a web-based, participatory planning tool that can be used to engage with watershed stakeholder communities, and involve them in using science-based, human-guided, interactive simulation–optimization methods for designing potential conservation practices on their landscape. The underlying optimization algorithms, process simulation models, and interfaces allow users to not only spatially optimize the locations and types of new conservation practices based on quantifiable goals estimated by the dynamic simulation models, but also to include their personal subjective and/or unquantifiable criteria in the location and design of these practices. In this paper, we describe the software, interfaces, and architecture of WRESTORE, provide scenarios for implementing the WRESTORE tool in a watershed community's planning process, and discuss considerations for future developments. Highlights: A participatory design tool that uses interactive and human-guided approaches to simulation–optimization. Tool can be used to engage stakeholders in assist with planning of conservation practices. Users can be engaged to view and evaluate designs based on quantifiable and un-quantifiable criteria. The software is web-based and can be used for engagement with individual users or multiple users.